Divine Attributes of the First Immobile Mover in Aristotle’s Physics - Rego, Thomas (Anales del Seminario de Historia de la Filosofía, 2023)
After an analysis of the various proofs of the first unmoved mover’s existence in Aristotle’s Physics, we are able to infer certain qualities emerging from them. These qualities are proper to what usually is considered a divine substance. Thus, from those proofs emerge two kinds of qualities: on the one hand, connected to the first unmoved mover’s transcendence respect of nature, appear its immutability, its eternity, its distance from the rest of beings, its being intelligence, its unicity, its possessing unlimited power, its immateriality, and, on the other hand, connected to its power over the world, appear its causality over the world’s movement, its dominion over the beings, its encompassing them, and, finally, its being cause of the being and not being of things. These two kinds of attributes find their connection in certain attribute, which has no name, thanks to which this agent is a ‘non-natural principle, which moves naturally’.